Demokrasi dan Kemakmuran - Aleksius Jemadu (Jurnal Administrasi Publik, 2004)
The Indonesia's economic growth which not recovered yet after the collapse of Orde Baru regime have led to pessimistic opinion on the on-going democratization in Indonesia. There is some hesitation whether or not the democratization is really can be a guarantee for the prosperity in this country. This article seeks to develop optimistic opinion by explaining the requirements must be established for the nation in order to reach the prosperity.Kata Kunci : demokratisasi, kemakmuran, democratic regime, governing institution